The company's value is influenced by profitability and liquidity - Yuliyanti, Dita; Masriyah, Masriyah; Mulyanah, Mulyanah; Haryadi, Didit; Wahyudi, Wahyudi (Trigin Publisher, 2024)
This study investigates the interaction between capital structure, net profit margin, and company value in the manufacturing sector in Indonesia. The goal is to gain insight into how these factors interact and affect the overall value of a company in a particular region and industry. This analysis uses quantitative methods based on financial data and relevant metrics for a sample of food and beverage sector companies operating in Indonesia from 2019 – 2023, with sample data of 15 companies having been used. This study examines the relationship between profitability, liquidity, and company value through statistical analysis and linear regression modeling techniques with SPSS version 26. The results showed that profitability had a significant effect on the value of the company. Liquidity does not affect the value of the company. Profitability and liquidity simultaneously affect the value of a company. The findings contribute to the existing literature on company valuations by providing empirical evidence specific to the food and beverage sector listed on the Indonesia Stock Exchange. The research has implications for policymakers, investors, and managers, as it offers valuable insights into the factors that drive corporate value in the industry, helping stakeholders make decisions and strategies to improve performance and competitiveness. Provide benefits in the context of financial management